DIGITAL TRANSFORMATION AS A PRIORITY ACTIVITY AT CHILDREN'S AND YOUTH SPORT SCHOOLS (Physical Culture and Sport: Scientific Perspective, 2022)
The article deals with determination of possibilities to use information and communication means for increase of activity efficiency of sports-profile extramural educational establishments. Taking into account the research of native and foreign scientists, it was established that the issues of digital transformation in the field of physical culture and sports have been studied partially.Inconsistency of the state of digital transformation of the sphere of home sports and physical culture with the modern trends of the development of sports in the world and the impossibility to perform actual tasks with existing methods without the use of information technologies has been established.Digital transformation (digitalization) means the act or process of digitization; conversion of analog data (images, video and text materials) into digital form; digitization - implementation or increase in the use of digital and computer technologies by organizations, in a certain industry, country etc.Seven indicators affecting the effectiveness and related to the digitalization of the activity of an extramural sports educational institution were singled out, namely: effective cooperation with patrons and sponsors; simplification of the procedure for obtaining a medical permit for training or participation in competitions in various sports through the development and implementation of a mechanism for the interaction of the athletes' electronic card with the medical electronic card; introduction of an electronic system of the sports growth of the athlete starting from the first coach and specialists related to his growth; transparent financing of both individual athletes and departments of Children’s and Youth Sports Schools on the basis of a public IT platforms and effective distribution of funds; determination of criteria for the efficiency of the departments of Children’s and Youth Sports Schools, digitization of their activities and transparent, automated distribution of funds; creation of a technical mechanism for receiving feedback on the quality of physical culture and health as well as sports services provided to the population and taking operational measures in case of detected violations; rating of athletes and their coaches takes place automatically; additional stimulation of the activity of coaching personnel.Polling of coaches-instructors was used to reveal the hierarchy of indicators of activity efficiency of Children’s and Youth Sports Schools.
Keywords: digitalization; Children’s and Youth Sports Schools; digital transformation